IMF Staff papers : Volume 22 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1975)
This detailed investigation of the effects of the devaluation of sterling by the United Kingdom in 1967 examines the critical economic relationships involved in devaluation and estimates them over a period which spans the devaluation (1960-1972). Perverse effects on the trade balance which occurred in the first half of 1968 were more than compensated for by favorable effects on private services and other invisibles. The 'cost' of the devaluation in terms of inflationary pressures and welfare losses was also high. The paper concludes that the favorable effect of the devaluation on the UK current balance has been seriously underestimated by the London Business School and to an even greater extent by the National Institute of Economic and Social Research in their well-known studies on the 1967 devaluation. They underestimated the effect mainly because they assumed, based on econometric work at a very aggregative level, that UK imports were not affected by relative price changes. Estimates of import price elasticities obtained at a more disaggregated level do not support this contention.